Comparitive Assessment of the Colour Enchancement Potential Of Indigenous Ornamental Flower Pigment Sources In the Sword Tail ,Xiphophorus Helleri - Adnankhan,Golandaj (School of Aquaculture And Biotechnology ,KUFOS, 2014)
Abstract- Colouration is a key factor deciding the market value of ornamental fish. In captive conditions, in the course of time, particularly when fed on pelleted diets, the colour of ornamental fish becomes dull, resulting in poor demand and low prices. Fishes do not biosynthesize carotenoids, but depend on dietary supplementation of carotenoids for colouration . A number of studies have been conducted on the enhancement of colour of ornamental fishes in captivity. Substances assessed for dietary enhancement of colour include carotenoids of plant as well as animal origin. The present study evaluates the possibility of utilizing locally available plant pigment sources namely flower meal of Marigold, Ixora and Hibiscus for enhancement of the colour of the sword tail, Xiphophorus helleri. The experiment was conducted on the larvae of sword tails for a period of 90 days. Completely randomized design was employed for the study. Dried petal meal of the three chosen ornamental sources was incorporated in the test diets at 5% each. The test diets were designated as T1, T 2 and T 3 respectively. A basal feed with no added carotenoid source served as the control (T0). The study was conducted indoors in fibre glass tanks of capacity45 l. Ten nos. of larvae were stocked in each tank. Each diet was fed to fish in a set of three tanks each. Growth response as well as water quality parameters were monitored at fortnightly intervals. The growth response was the highest in marigold supplemented diets followed by ixora and hibiscus supplemented diets. The colour enhancement was assessed by colorimetry as well as by employing computer assisted approach, employing Adobe Photoshop® Version 7. On termination of the study, the growth data was statistically analysed using two way analysis of variance. Fish fed all the three test diets showed significantly different growth response from the control fish. Significant enhancement in colour development was observed in fish fed all three test diets. The intensity of colour development was highest in T1 treatment followed by T2 and T3. Fish fed the control diet showed the least colour intensity. The three flower meals assessed are cheap, easily available and involve only marginal additional cost. This approach is easily adoptable at the farmer level and moreover, does not involve any adverse effects . Further studies are required on the optimum level of inclusion of the carotenoid sources in the diets.